2022
DOI: 10.1017/jfm.2022.453
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and bifurcations of laminar annular swirling and non-swirling jets

Abstract: This paper presents bifurcation analyses characterising the nonlinear dynamics of fully developed laminar annular jets with respect to the centrebody diameter ${ {d}}$ , Reynolds number ${ {Re}}$ , and swirl ratio ${ {S}}$ . Similar flows appear in numerous applications and feature a vibrant range of topological and dynamical characteristics associated with phenomena including shear layer separation and vortex breakdown. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 72 publications
(207 reference statements)
0
1
0
Order By: Relevance
“…In a recent pair of studies led by the first author, bifurcation analysis was used to investigate the steady and time-periodic dynamics of radially unconfined laminar swirling jets issuing from rotating pipes mounted flush against a semi-infinite axial wall (Douglas, Emerson & Lieuwen 2021, 2022). Those studies demonstrated that in the steady regime, an axisymmetric CRZ emerges gradually in the quasi-columnar jet due to vortex breakdown as the swirl ratio is increased.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent pair of studies led by the first author, bifurcation analysis was used to investigate the steady and time-periodic dynamics of radially unconfined laminar swirling jets issuing from rotating pipes mounted flush against a semi-infinite axial wall (Douglas, Emerson & Lieuwen 2021, 2022). Those studies demonstrated that in the steady regime, an axisymmetric CRZ emerges gradually in the quasi-columnar jet due to vortex breakdown as the swirl ratio is increased.…”
Section: Introductionmentioning
confidence: 99%